Quantitation of baby wipes lotion transfer to premature and neonatal skin. (October 2015) - Hossain, Md Monir; Jones, Jennifer M.; Dey, Swatee; Carr, Gregory J.; Visscher, Marty O.
Abstract: Exposure to topically applied substances occurs routinely in premature and hospitalized infant care. Safety determinations are most accurate when exposures are based on appropriately designed studies to capture variations in practice patterns and population heterogeneity. Current safety assessments may not reflect actual practice resulting in overly conservative or understated default assumptions for toxicological determinations. We quantified the amount of baby wipes lotion transferred to premature and term neonatal skin as grams/kg body weight/day. We observed the soil type and number of wipes used for skin cleansing and measured lotion transfer from one wipe applied to freshly clean, dry skin. A Bayesian imputation approach was applied to compute lotion exposure and produce summary statistics. Model covariates were age and weight at evaluation, gender, soil type, soil amount, and number of diaper changes per day. Lotion transfer was measured for 66 premature and 55 term neonates with 449 and 254 evaluations, respectively. The wipes per day was 12.52 overall (all infants and soils), 12.78 for premature and 12.21 for term neonates. Lotion transfer was 0.20 g/kg/day (95th percentile) overall, 0.21 for premature and 0.19 for term neonates. The statistical and experimental methodology represents an effective strategy for determining exposure and assessing risk. Highlights: Wipes lotion transferred to neonatal skin was determined as grams/kg/day. The data were generated for use in toxicological exposure-based risk assessments. The premature neonates were over-represented to ensure robust data for this group. Bayesian imputation was used to ascertain lotion transfer at every diaper change. The exposure method can be reapplied to questions about other topical agents.